2020
DOI: 10.3126/nmj.v3i1.28923
|View full text |Cite
|
Sign up to set email alerts
|

Fetomaternal Outcome in Second Stage Caesarean Section

Abstract: Introduction: Second stage caesarean section is usually associated with the deeply engaged head, less liquor, and thinned out the lower uterine segment. This can lead to a high risk of maternal morbidities like an extension of the lower uterine segment incision, uterine atony, and injury to urinary bladder as well as neonatal morbidities such as birth asphyxia, NICU admission, and meconium aspiration syndrome. This study aims to observe the maternal and neonatal outcomes of caesarean delivery performed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Sameer et al also reported the same findings. [15][16][17][18][19][20][21][22][23][24][25][26][27] A retrospective study from Canada has shown that women delivered by caesarean sections at full dilatation of the cervix were 2.6 times more likely to have intraoperative trauma. 10 These difficulties were due to the edematous lower segment, overstretched and thinned-out lower segment, and impaction of presenting part in the pelvis as the duration for the second stage increases.…”
Section: Discussionmentioning
confidence: 99%
“…Sameer et al also reported the same findings. [15][16][17][18][19][20][21][22][23][24][25][26][27] A retrospective study from Canada has shown that women delivered by caesarean sections at full dilatation of the cervix were 2.6 times more likely to have intraoperative trauma. 10 These difficulties were due to the edematous lower segment, overstretched and thinned-out lower segment, and impaction of presenting part in the pelvis as the duration for the second stage increases.…”
Section: Discussionmentioning
confidence: 99%
“…In general, caesarean delivery is associated with more severe maternal complications compared to vaginal deliveries. 2,3 The stage of labour at rate/risk of complication. 4 As the CS rate is rising everywhere, so is the incidence of second-stage CS.…”
Section: Introductionmentioning
confidence: 99%
“…Cesarean section (CS) is the delivery of the fetus through incisions in the abdominal and uterine walls and is considered an alternative to vaginal delivery [1][2][3]. Recent data demonstrate that the prevalence of CS is increasing rapidly with second-stage CS from 0.9% to 2.2% [4,5]. The second stage of labor which usually used to last two hours begins with full cervical dilation that is 10 cm and completes with the delivery of the fetus [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Either emergency or an elective CS, both are more likely to experience complications than a typical vaginal delivery. Owing to the complexity of CS in the second stage of labor, it is technically challenging to accomplish due to the profoundly impacted head of the fetus in the pelvis, the lack of liquor, and the occurrence of the oedematous thin segment at a lower level [5,9,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation